A Simple Photometer as a Helping Device in Measuring Blood Glucose - Aryo Tedjo; Erfi Prafiantini; Akmal P. Suprapto; Anwar S. Ibrahim; Subari A. Riyanto; Dendi Priyanto (Makara Journal of Health Research, 2014)
Measurement of non-invasive blood glucose is one way to increase the frequency of self-monitoring of blood glucose (SMBG). For NIR reflectance spectroscopy, its application in non-invasive constrained by high value of standard error of prediction. The mean standard error of prediction was 25 mg/dL. Theoretically, NIR reflectance spectroscopy still can be used to predict blood glucose levels in certain conditions such as hypoglycemia (<55 mg/dL), controlled fasting blood glucose (FBG) (70-115 mg/dL), and hyperglycemia (>225 mg/dL), which the difference between the three conditions is more than 25 mg/dL. The results showed that there are significant differences in standards values of photometer measurement between controlled FBG and hyperglycemic conditions (P = 0.002). The results also showed that the photometer can be used to assist the monitoring of blood glucose in FBG under control and hyperglycemic conditions. It can be seen from the average percentage of the daily controlled FBG conditions in patients conducting SMBG in photometer-assisted compared to in patients only use SMBG once a day (28% versus 18%, P = 0.344).